Transparency in African Microfinance Institutions - Marconatto, Diego Antonio Bittencourt; Barin-Cruz, Luciano; Legoux, Renaud (Revista de Administração da UFSM, 2018)
The lack of transparency in African microfinance institutions (MFIs) is believed to delay the dissemination of microfinance in the continent. In this study, we focus on the question of how organizational characteristics and governmental corruption influence the transparency of African MFIs. Our results show that MFIs’ maturity and larger size improve transparency in African MFIs, while a nonprofit status or a focus on small businesses do not lead to the same improvement. Regulation, in turn, makes African MFIs less transparent. Our findings also reveal the impact of governmental corruption on the relationship between organizational characteristics and MFIs’ transparency in Africa: less corruption enhances the transparency of all MFIs, excepting for the regulated ones. Finally, we show that in countries with high levels of corruption, the MFIs that should be supported in becoming more transparent are the nonprofits, those dedicated to small businesses, and the regulated MFIs.